Innovative Improvement in the Physical Education Learning Experience: A Study at Dela Paz National High School Philippines - Tianio, Jomar Seguro; De Castro, Jefferson Moreno (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This study aims to investigate the impact of innovative teaching approaches, specifically learning and the utilization of technology, on students' academic performance and their development of critical thinking skills, leadership skills, social skills, and values. The Physical Education program offered at Dela Paz National High School serves as a case study to illustrate the implementation of these strategies. This research utilizes mixed methods. Collecting data using survey and qualitative data are collected through in-depth teacher interviews and focus group discussions with students. Descriptive statistics is utilized to analyze the survey data, providing a quantitative overview. The study reveals that these innovative approaches have significantly contributed to the overall development of students, including improvements in academic achievement, critical thinking abilities, leadership competencies, social skills, and values. The findings of this research highlight the potential of innovative teaching methods to address limitations in equipment and facilities, leading to enhanced learning experiences and holistic student development. Collaborative partnerships with local businesses and organizations, integrating technology and digital resources, and promoting resource sharing among educational institutions emerge as effective strategies to overcome resource constraints. By prioritizing the implementation of these innovative approaches, educational institutions can better prepare their students for success in various aspects of their lives. This study emphasizes incorporating innovative teaching methods to foster a comprehensive and well-rounded educational experience. By leveraging service learning and technology, educational institutions can create an environment that enhances students' learning outcomes and improves their overall development.